2023
DOI: 10.1002/glia.24392
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and multifaceted ATP release from astrocytes at the scale of hundreds of synapses

Abstract: Astrocytes participate in information processing by releasing neuroactive substances termed gliotransmitters, including ATP. Individual astrocytes come into contact with thousands of synapses with their ramified structure, but the spatiotemporal dynamics of ATP gliotransmission remains unclear, especially in physiological brain tissue. Using a genetically encoded fluorescent sensor, GRAB ATP1.0 , we discovered that extracellular ATP increased locally and transiently in absence of stimuli in neuron-glia co-cult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Serum-deprivation lowered both ATP and CrP levels in cultured astrocytes, suggesting that serum contains compounds which support the maintenance of high cellular levels of both compounds. A loss in cellular ATP and CrP of astrocytes under such conditions is not unexpected as some cellular CrP is likely to disappear by spontaneous formation of creatinine [ 57 ] and as ATP can be exported from astrocytes [ 58 , 59 ]. Serum components may be used by astrocytes to compensate for these losses.…”
Section: Discussionmentioning
confidence: 99%
“…Serum-deprivation lowered both ATP and CrP levels in cultured astrocytes, suggesting that serum contains compounds which support the maintenance of high cellular levels of both compounds. A loss in cellular ATP and CrP of astrocytes under such conditions is not unexpected as some cellular CrP is likely to disappear by spontaneous formation of creatinine [ 57 ] and as ATP can be exported from astrocytes [ 58 , 59 ]. Serum components may be used by astrocytes to compensate for these losses.…”
Section: Discussionmentioning
confidence: 99%
“…GRAB ADO1.0 permits analysis of adenosine dynamics in the sleep–wake cycle by in vivo fiber photometry ( Peng et al, 2020 ). GRAB ATP1.0 expressed in astrocytes detects the spontaneous release of ATP, some of which seems to occur locally ( Hatashita et al, 2023 ). ATP1.0-L sensor, an ATP sensor with lower affinity and faster kinetics, may be useful to detect local release of ATP ( Wu et al, 2022b ).…”
Section: Methods Of Measuring Extracellular Atp/adenosinementioning
confidence: 99%
“…Dopamine increases Ca 2+ signal events in astrocytes, suggesting a Ca 2+ -dependent mechanism underlies the ATP events. Hatashita et al examined spontaneous ATP dynamics in situ in the presence of TTX and in anesthetized mice using GRAB ATP1.0 ( Hatashita et al, 2023 ). The investigators found spatiotemporally diverse types of spontaneous ATP events.…”
Section: Extracellular Atp/adenosine Increases Induced By Neuronal Ac...mentioning
confidence: 99%
See 1 more Smart Citation
“…Astrocytes tightly and dynamically interact with synapses having a critical role in synaptic information processing (Araque et al, 1999; Araque et al, 2014; Durkee & Alfonso, 2019; Guerra‐Gomes et al, 2018; Perea et al, 2009; Perea & Araque, 2005), ultimately playing a critical function in cognitive (Kofuji & Araque, 2021), anxiety (Cho et al, 2022) and depressive‐like behavior (Banasr & Duman, 2008). A key step in the interaction between astrocytes and neurons is the calcium (Ca 2+ )‐dependent release of gliotransmitters, such as glutamate (de Ceglia et al, 2023; Navarrete & Araque, 2008; Perea et al, 2016), ATP (Gordon et al, 2005; Hatashita et al, 2023; Xiong et al, 2018), GABA (Le Meur et al, 2012), and D‐serine (Abreu et al, 2023; Henneberger et al, 2010; Robin et al, 2018), which in turn is triggered by a wide variety of membrane receptors for neurotransmitters and neuromodulators, including glutamate (Skowrońska et al, 2019), ATP (Baraibar et al, 2023; Jacob et al, 2014), GABA (Jiménez‐Dinamarca et al, 2022; Le Meur et al, 2012), and endocannabinoids (eCBs) receptors, among others (Corkrum et al, 2020; Perea et al, 2009; Volterra & Meldolesi, 2005).…”
Section: Introductionmentioning
confidence: 99%